Objective and subjective components of the first-night effect in young nightmare sufferers and healthy participants. - Kis, A; Szakadát, S; Simor, P; Gombos, F; Horváth, K; Bódizs, R (2014)
The first-night effect--marked differences between the first- and the second-night sleep spent in a laboratory--is a widely known phenomenon that accounts for the common practice of excluding the first-night sleep from any polysomnographic analysis. The extent to which the first-night effect is present in a participant, as well as its duration (1 or more nights), might have diagnostic value and should account for different protocols used for distinct patient groups. This study investigated the first-night effect on nightmare sufferers (NM; N = 12) and healthy controls (N = 15) using both objective (2-night-long polysomnography) and subjective (Groningen Sleep Quality Scale for the 2 nights spent in the laboratory and 1 regular night spent at home) methods. Differences were found in both the objective (sleep efficiency, wakefulness after sleep onset, sleep latency, Stage-1 duration, Stage-2 duration, slow-wave sleep duration, and REM duration) and subjective (self-rating) variables between the 2 nights and the 2 groups, with a more pronounced first-night effect in the case of the NM group. Furthermore, subjective sleep quality was strongly related to polysomnographic variables and did not differ among 1 regular night spent at home and the second night spent in the laboratory. The importance of these results is discussed from a diagnostic point of view.